Transforming Islamic Education: The Role of Islamic Religious Education (IRE) Teacher Leaders in Designing Learning Materials at Lhokseumawe Junior High Schools - Syarifah Rahmah; Diana; K.J Vargheese; Fitriani; Edo Alvizar Dayusman (Jurnal Pendidikan Agama Islam, 2025)
Objective - The Merdeka Curriculum requires IRE Teacher Leader (Guru Penggerak Pendidikan Agama Islam) to develop pedagogical creativity in designing contextual and student-centered learning materials. However, current IRE teaching practices in schools still show limited variety and optimization of learning materials, meaning that the integration of Islamic values with the objectives of the Merdeka Curriculum has not yet been fully achieved. This study aims to analyze the role of IRE Teacher Leader in designing, adapting, and evaluating learning media based on the Merdeka Curriculum at the junior high school level in Lhokseumawe City. Design/method/approach - This study employed an exploratory qualitative approach involving three IRE Teacher Leaders, supported by Vice Principals for Curriculum and IRE Teacher Leader Coordinators at Public Junior High Schools A, B, and C in Lhokseumawe City as informants representing pilot schools. Data were collected through semi-structured interviews, participatory observation, and document analysis, then analyzed using thematic analysis with method triangulation to ensure validity. Findings - The research findings indicated that IRE Teacher Leader possess professional awareness in planning instructional media and are capable of adapting it to the characteristics of students and the context of IRE instruction. Instructional media is used to support social interaction, the internalization of religious values, and more contextual learning. However, this study also found that these practices still face a number of obstacles, including limited technology-based creativity, weak collaboration among teachers in media development, and the lack of systematic and continuous evaluation of learning media. These conditions indicate a gap between the ideal role of IRE Teacher Leader as learning leaders and the implementation of learning media in practice. Research implications/limitations - These findings indicated the need to strengthen techno-pedagogical capacity, provide media evaluation training, and foster a collaborative culture through school-policy-based Professional Learning Communities (PLC). Originality/Value - This study offers an original contribution by integrating the perspectives of Islamic education, the Merdeka Curriculum policy, and the role of IRE Teacher Leader as agents of value-based educational change.